Efecte ale migraţiei internaţionale asupra locuirii în ruralul românesc. Cazul comunei Marginea, judeţul Suceava, România - Jacob (Larionescu), Andra (Calitatea Vieții, 2015)
The paper rely on a qualitative research launched in the summer of 2009, part of a doctoral research project in sociology, which aimed to observe the houses built by migrants from rural areas. The paper is purely descriptive, tracing the impact of international migration on rural housing in Romania in general and, in particular, in the village of Marginea. The paper is structured around five sections. The first part sets up the place and the role of the house within the international migration context, while the second part includes the data and methods used in my fieldwork. The two sections, which follow, describe the field and illustrate the impact of international migration on housing in migrants’ homeland. Finally, I present a short summary of the ways in which migration changed the built landscape on migrants’ homeland.